At the origins of school integration: A case study in the Pratozanino Asylum - Anita Maugeri (Pensa MultiMedia, 2022)
The study in question analysed the educational methods directed towards the children recovering at the Pavilion 10 of Pratozanino Asylum in Cogoleto, in the Province of Genoa, during the period between 1887, the year the facility opened, until about 1940. In this case, the attempt at school integration was covered in two ways: through the classroom, inside the structure, and through the official school system in which Giuseppe Vidoni, a psychiatrist, supported the importance in the attendance of the children, considered abnormal, into the multi-classes of Pratozanino. In order to give a better understanding to the reader, I have chosen to use, within the text, the terminology present in the original documentation.